AKOMODASI BUDAYA LOKAL (`URF ) DALAM PEMAHAMAN FIKIH ULAMA MUJTAHIDIN - Iim Fahimah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2018)
Culture is a set of human knowledge that is used as a guide or to interpret the overall human actions. Culture is also a guideline for people's lives which is believed to be true by the community. As a pattern for action, culture contains a set of knowledge possessed by humans as social beings, whose contents are devices, models of knowledge that are selectively used to understand and interpret the environment faced and to encourage and create necessary actions. Whereas as a pattern of action, culture is what happens in the daily lives of people based on guidelines believed to be true. Furthermore, in order to ground Islam to society so that the concept of Islamic law becomes a handle in interacting, accommodating local culture in Islamic law is a must. Acceptance of f urf as one of the arguments in establishing Islamic law provides an opportunity for the dynamics of Islamic law. Because many problems are not accommodated in the method of qiyas, istihsan, mashlahah mursalah and others, can be accommodated by ‘urf (local culture). Scholars accommodate local culture which in some ways is difficult to deny its need for that culture